Growth of amorphous domains in precursor derived Si-C-N-Ceramics studied with small angle X-ray scattering - Gruber, Wolfgang; Starykov, Oleksiy; Oppermann, Wilhelm; Schmidt, Harald (Diffusion Fundamentals, 2008)
Amorphous precursor derived ceramics with the composition Si26C41N33 were isothermally annealed at 1500 °C for 5 minutes up to 190 minutes. Two series of measurements were carried out: one at a nitrogen partial pressure of 1 bar and one at a nitrogen partial pressure of 1 mbar. Small angle X-ray scattering was used to determine the diameter of the amorphous domains. The Guinier radius was found to vary from 9.5 Å to 13 Å irrespective of the partial pressure of nitrogen. This finding is quite surprising since crystallization of this material strongly depends on the partial pressure of nitrogen.